Evaluating Potential Economic Effects of an Industrial Road on Subsistence in North-Central Alaska - Guettabi, Mouhcine; Greenberg, Joshua; Little, Joseph; Joly, Kyle (ARCTIC, 2016)
North-central Alaska is one of largest inhabited, roadless areas in North America and, indeed, the world. Access, via a new road, to the Ambler mining district of north-central Alaska has been proposed. To evaluate how new road access might affect subsistence harvest, we used zero inflated negative binomial models to identify factors related to subsistence production at the household level. We found substantial differences in these factors between communities near the proposed road (project zone [PZ] communities) and a comparable set of road accessible communities outside the region (non-project zone [NPZ] communities). Total subsistence production of PZ communities was 1.8 to 2.5 times greater than that of NPZ communities. If the road was opened to the public and subsistence harvest patterns for project zone communities changed to mirror existing non-project zone harvests as a result of the road, the financial cost would be USD $6900–10 500 per household (assuming a $17.64/kg “replacement” cost for subsistence harvests). Taken together, our results suggest that the proposed road should be expected to substantially impact subsistence production in communities that are not currently connected to the road system. Le nord-ouest de l’Alaska est l’une des plus grandes régions habitées de l’Amérique du Nord, voire du monde, qui n’a pas de routes. Une nouvelle route a été proposée pour donner accès à cette région de même qu’au district minier Ambler dans le centre-nord de l’Alaska. Afin d’évaluer l’effet de l’accès que procurerait cette nouvelle route sur les récoltes de subsistance, nous nous sommes servis de modèles binomiaux négatifs à inflation de zéros pour déterminer les facteurs se rapportant à la production de subsistance des ménages. Nous avons relevé des différences considérables sur le plan de ces facteurs entre les communautés situées près de la route proposée (les communautés de la zone du projet [PZ]) et un ensemble comparable de communautés accessibles par voie routière à l’extérieur de cette région ...